A MODEL AND IMPLEMENTATION OF ACADEMIC DATA INTEGRATION IN NEAR-REAL TIME USING MESSAGE-ORIENTED MIDDLEWARE TO SUPPORT ANALYSIS OF STUDENT PERFORMANCE IN THE INFORMATION TECHNOLOGY DEPARTMENT OF POLITEKNIK CALTEX RIAU - Yuni Tjung; Ardianto Wibowo; Muhammad Arif Fadhly Ridha (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2020)
Data utilization has effectively contributed for institutions growth by providing insights for managerial purposes. In Information Technology (IT) Department of Politeknik Caltex Riau, information systems were built separately, makes it hard for the head of study program to analyze academic performance. For analytical purposes, there’s a business intelligence developed to equip each head of study programs in IT Department with knowledge about their department. Unfortunately, the business intelligence hasn’t considered with data integration. To solve this problem, this research proposes 2 different academic near-real time data integration model that are documented using Enterprise Integration Pattern and benchmarkes the implementation to obtain best data integration model. The models use Message-Oriented Middleware, a technology that enables asynchronous communication between diverse applications. This research uses WSO2 ESB as the MOM tools in Service-Oriented Architecture (SOA) that use NuSOAP library for helping generating web service WSDL and will use Enterprise Application Integration approach. The testing is conducted based on ISO 9126 aspects: functionality, efficiency, and reliability. Based on the testing results, it can be concluded that both integration models fulfill the functionality and reliability aspects, but the 2nd pattern is more efficient because it distincts message channel and store for each dimension and fact table.